What Motivates Parents to Participate in Their Child’s Brain Gym Therapy - Nadhira Rakhmi Yusuf; Zainal Abidin (Bisma The Journal of Counseling, 2021)
The findings in the clinical practice field indicate problems related to the inconsistency of parental participation in the therapy that the child undergoes, namely the absence of parents according to the schedule, non-adherence to the therapist's advice, and premature termination. It raises questions of parents' motivation to participate in their children's therapy while no research in Indonesia examines this topic. The current study aims to understand the description of parents' motivation to participate in their child therapy. This qualitative study was conducted by interviewing 3 mothers (age 23-36 years) whose children (age 3-5 years) undergo brain gym therapy at a psychology bureau in Bandung. They are from the same socioeconomic class, have joined the therapy program for at least one month, and were selected using the purposive sampling technique. The results indicate that the underlying motivation for parental participation in child therapy is parents' need for a change in the child's condition and parents' expectation of the therapeutic outcome. Therapy results that match expectations and positive responses from the environment act as reinforcers that make parents willing to continue participating in child therapy.